Spirituality, Moral Identity, and Consumer Ethics: A Multi-cultural Study - Vitell, Scott J. (Journal of business ethics, 2016)
This article presents the results of a cross-cultural study that examines the relationship between spirituality and a consumer’s ethical predisposition, and further examines the relationship between the internalization of one’s moral identity and a consumer’s ethical predisposition. Finally, the moderating impact of cultural factors on the above relationships is tested using Hofstede’s five dimensions. Data were gathered from young adult, well-educated consumers in five different countries, namely the U.S., France, Spain, India, and Egypt. The results indicate that the more spiritual an individual consumer is, the more likely that consumer is to be ethically predisposed. Furthermore, the stronger one’s internalization of a moral identity, the more likely one is to be ethically predisposed. These two relationships are further moderated by Hofstede’s cultural factors such as the degree of collectivism versus individualism in the culture. However, the strength and direction of the moderation may vary depending upon the specific Hofstede dimension.